JsNMR: an embedded platform‐independent NMR spectrum viewer. (12th January 2015) - Vosegaard, Thomas
Abstract : jsNMR is a lightweight NMR spectrum viewer written in JavaScript/HyperText Markup Language (HTML), which provides a cross‐platform spectrum visualizer that runs on all computer architectures including mobile devices. Experimental (and simulated) datasets are easily opened in jsNMR by (i) drag and drop on a jsNMR browser window, (ii) by preparing a jsNMR file from the jsNMR web site, or (iii) by mailing the raw data to the jsNMR web portal. jsNMR embeds the original data in the HTML file, so a jsNMR file is a self‐transforming dataset that may be exported to various formats, e.g. comma‐separated values. The main applications of jsNMR are to provide easy access to NMR data without the need for dedicated software installed and to provide the possibility to visualize NMR spectra on web sites. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : jsNMR is a lightweight NMR spectrum viewer written in JavaScript/HTML available in most web browsers on any computer platforms including mobile devices, thereby offering spectrum visualization without the need for dedicated software installed. In addition to the visualization, jsNMR embeds the original data in the HTML file and features outtput to a number of other formats, so a jsNMR file is a self‐transforming dataset.